EDUCATION POLICY AND EFL CURRICULUM IN INDONESIA: BETWEEN THE COMMITMENT TO COMPETENCE AND THE QUEST FOR HIGHER TEST SCORES - Anita Lie (TEFLIN, 2007)
Education policies and curricula provide the context and specific expectations that drive student learning and achievement towards a sustainable future. The underlying policies and practices in the EFL classrooms do not always match consistently. There is an emerging need to counterbalance the power of policymakers in ensuring that balanced, pedagogically sound education policies and EFL curriculum are produced, carried out, and monitored. As one of civil society organizations, TEFLIN is well positioned to serve that mission. TEFLIN may take the initiative to engage in the EFL curriculum review project, EFL curriculum design, and reform in EFL teacher education and certification.